Downregulation of PAQR3 expression predicts poor prognosis of patients with pan-cancer: a meta-analysis - Zhai, Kui; Miao, Xing-Peng; Ai, Shi-Gui; Guo, Qiang; Zha, Ren-Zhong (Frontiers in Oncology, 2025)
This study aimed to evaluate the association between progestin and adipoQ receptor 3 (PAQR3) expression and survival outcomes, as well as disease progression, through a meta-analysis. A systematic literature search was conducted across multiple academic databases, including Cochrane Library, Embase, PubMed, Web of Science, and Google Scholar. Relevant studies were identified and screened based on predefined inclusion and exclusion criteria. Statistical analyses, including odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs), were employed to assess the relationship between PAQR3 expression levels and prognostic outcomes, as well as clinicopathological features in pan-cancer patients. A total of 1032 patients from nine eligible studies were included in the meta-analysis. The results demonstrated that high PAQR3 expression was significantly associated with improved overall survival (HR = 0.32; 95% CI = 0.19–0.56) and disease-free survival (HR = 0.35; 95% CI = 0.20–0.61) in pan-cancer patients. Downregulation of PAQR3 expression was significantly correlated with adverse clinicopathological characteristics, including lymph node metastasis (HR = 0.22; 95% CI = 0.06–0.82), higher histological grade (HR = 0.31; 95% CI = 0.12–0.81), advanced pathological stage (HR = 0.18; 95% CI = 0.05–0.66), tumor size (HR = 0.73; 95% CI = 0.36–1.5), distant metastasis (HR = 0.36; 95% CI = 0.07–1.82), and tumor invasion (HR = 0.18; 95% CI = 0.11–0.29). However, no significant associations were observed between PAQR3 expression and gender (HR = 0.94; 95% CI = 0.59–1.5) or age (HR = 1.10; 95% CI = 0.77–1.56). In conclusion, reduced PAQR3 expression in pan-cancer patients is associated with worse clinical outcomes and may promote cancer progression. These findings suggest that PAQR3 could serve as a potential prognostic biomarker and therapeutic target for cancer treatment.